Structural Equation Model to Measure the Leveraging Factors of Research Productivity in Private Universities: Lecturers' Perceptions - Harahap, Hadry; Andriani, Dewi; Oemar, Harris (International Journal of Scientific Research and Management (IJSRM), 2020)
Lecturers play an important role in carrying out tasks that are neatly packaged in the Tri Dharma Perguruan Tinggi which consists of conducting research, writing, and publishing the results of their research in reputable journals and providing service to the surrounding community according to the subject specialization of individuals. The purpose  of this study is to determine. Structural Equation Model to Measure the Leveraging Factors of Research Productivity in Private Universities: Lecturers' Perceptions  This study was conducted to test the proposed hypothesis using quantitative research methods and was designed according to the variables to be studied. as well as data analysis techniques using SEM with IBM AMOS 2 software. Based on the results of the analysis, it can be concluded that a new model was found on the positive direct effect of the reward system, transformational leadership style, communication, and motivation on productivity.